Longitudinal alcohol consumption patterns and health‐related quality of life: Results from the National Epidemiologic Survey on Alcohol and Related Conditions. (14th March 2017) - Imtiaz, Sameer; Loheswaran, Genane; Le Foll, Bernard; Rehm, Jürgen
Abstract: Introduction and Aims: Given the limited nature of the evidence concerning longitudinal alcohol consumption patterns and health‐related quality of life (HrQoL), this study examined these associations. Design and Methods: Data were from the National Epidemiologic Survey on Alcohol and Related Conditions (waves 1 and 2). Multiple linear regression was used to assess the associations between longitudinal alcohol consumption patterns (abstainers, no consumption change, decreased consumption, increased consumption, ceased consumption and initiated consumption) and HrQoL (Short‐Form 12‐Item Health Survey). Results: Increased consumption over follow up was related to non‐significant reductions in mental HrQoL for moderate and heavy drinkers at wave 1, whereas decreased consumption coincided with improvements in mental HrQoL for heavy drinkers at wave 1 (β for Mental Health Summary Scale and Mental Health Subscale: 0.84 and 0.91; P‐values significant for both scales). Similarly, initiation of consumption among lifetime abstainers at wave 1 was associated with reductions in mental HrQoL (β for Mental Health Summary Scale, Vitality Subscale, Social Functioning Subscale and Mental Health Subscale: −1.50, −1.89, −0.86 and −1.74; P‐values significant for all scales). On the other hand, cessation of consumption was accompanied by reductions in physical HrQoL (β for Physical Health Summary Scale, Physical Functioning Subscale, Role Physical Subscale, Bodily Pain Subscale and General Health Subscale: −1.29, −1.11, −1.35, −0.87 and −0.88; P‐values significant for all scales). Discussion and Conclusions: Increased or decreased consumption were inversely associated with mental HrQoL, but decreased consumption was also associated with reductions in physical HrQoL. These findings were confirmed by the ceased consumption and initiated consumption patterns. [Imtiaz S, Loheswaran G, Le Foll B, Rehm J. Longitudinal alcohol consumption patterns and health‐related quality of life: Results from the National Epidemiologic Survey on Alcohol and Related Conditions. Drug Alcohol Rev 2018;37:48–55]